Correlation of Neutrophyl-Lymphocyte Ratio, Vessel Score based on Sullivan Scoring System, and Troponin in Acute Coronary Syndrome Patients - Chelssi Gloria Tessari; Achmad Lefi; Yetti Hernaningsih (Cardiovascular and Cardiometabolic Journal, 2022)
Acute Coronary Syndrome (ACS) is one of the highest causes of death globally, with the number of deaths reaching more than 9 million people in 2016. Therefore, a fast and accurate ACS diagnosis is needed. This study aimed to determine the relationship between the neutrophil-lymphocyte ratio, the number of coronary artery lesions evaluated by angiography, and troponin I in ACS patients Material and Methods: This research is an analytic observational with a retrospective cross-sectional design. Sampling was carried out using a total sampling technique and obtained 87 samples that met the inclusion and exclusion criteria for the 2019-2020 period at Dr. Soetomo Regional General Hospital Surabaya. The correlation between the number of coronary artery lesions and the neutrophil-lymphocyte ratio to troponin I levels were respectively analyzed using chi-square and spearman-rho with SPSS ver. 25. Results: The results showed a moderately significant correlation between the neutrophil-lymphocyte ratio and troponin I levels (p =0.003, rs = 0.319). While the correlation analysis between the number of coronary artery lesions and the vessel score on troponin I showed insignificant results (p = 0.525), which means that the number of coronary artery lesions was not correlated with troponin I. Conclusion: This study concludes a significant correlation with moderate correlation between the neutrophil-lymphocyte ratio and troponin I. However, there is no significant correlation between the number of coronary artery lesions assessed by the Sullivan and troponin I levels.